ANALISIS KUALITAS PELAYANAN PUBLIK PADA KANTOR CAMAT PONTIANAK UTARA KOTA PONTIANAK - maulana Filani Rizal; SELVIANUS VENUS AFEN (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2021)
This research aims to analyze the Quality of Public Service at the North Pontianak District Office. The research method the authors used in this study is a survey study that takes samples from a population and uses questionnaires as a data collection tool. The population in this study is 2026, given the time and cost limitations that the authors took samples using Slovin theory. The samples in this study are people who have requested services to the North Pontianak District Office. Based on the results of the analysis, obtained the results of all average answers scores of respondents who were summed up got an average score of 21.10 and then the average number of scores divided by the number of 5 indicators then obtained an average of 4.22 and entered into a very good category. So it can be concluded that the quality of public service in the pontianak district office north of Pontianak city is in the category very well.